2020
DOI: 10.1111/jocn.15375
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological diseases, sexuality and intimate relationships: A qualitative meta‐synthesis

Abstract: Aims and objectives To conduct a systematic review and meta‐synthesis of findings from qualitative research about sexuality and intimate relationship among patients with dermatological diseases. Background Over the last few decades, there has been an increase in clinical research investigating aspects related to sex and sexuality in patients living with dermatological diseases. In fact, studies recognise a negative impact on various aspects of intimacy, such as sexual function, self‐esteem and romantic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The literature is predominantly based on HCPs’ views and not on patients’ views. Studies have covered views of oncology, 10–12 cardiovascular disease, 13 rheumatology, 14 and dermatology patients, 15 but no literature was found on views of those living with IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is predominantly based on HCPs’ views and not on patients’ views. Studies have covered views of oncology, 10–12 cardiovascular disease, 13 rheumatology, 14 and dermatology patients, 15 but no literature was found on views of those living with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants’ perceptions are consistent with those of oncology, rheumatology, heart disease, and dermatology patients. 11 , 12 , 14 , 15 Participants in cancer studies wanted to be asked about their sexuality issues and preferred to receive information on the topic from their HCP. 17 , 24 One barrier was the perceived lack of interest from HCPs in discussing sexuality/sexual well-being with the participants.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Critical Appraisal Skills Programme (CASP): it provides ten simple guiding questions and examples to examine study validity, adequacy, and potential applicability of the results of qualitative studies. Guided by the work of Long and colleagues [32] and previously used in other meta-synthesis [33], we created 30 items from the 10 CASP questions on quality to ensure we could provide a detailed appraisal of the studies. FDV and LD independently assessed the quality of included studies with any conflicts solved by consulting a third reviewer (MCB and LG).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The characteristics of included studies are reported in Table 1. Of these studies, 127 represented original work, and seven were systematic reviews ( Ablett and Thompson, 2016 ; Barisone et al., 2020 ; Ip et al., 2021 ; Nakayama et al., 2016 ; Singh et al., 2019 ; Sumpton et al., 2020 ; Teasdale et al., 2021 ). Studies occurred in 23 countries, with the majority conducted in the United Kingdom and the United States (49 of 134, 36.6% and 43 of 134, 32.1%, respectively).…”
Section: Resultsmentioning
confidence: 99%